Chemical and physical parameters supporting the top-rated product of Kapi-pla, a gastronomy of southern food, Thailand - Sunisa Siripongvutikorn; Kanyamanee Pumethakul; Jinattita thantrirat; Nualpun Sirinupong; Worrapanit Chansuwan; Worapong Usawakesmanee; Chanonkarn Rujirapong (Journal of Agriculture and Food Research)
“The Lost Taste Project”, Kapi-pla, fermented fish from Pak Phanang (Nakhon Si Thammarat) was declared the product champion based on committee judgment and popular vote without scientific information record even though it is regularly consumed in the south of Thailand. This present work aims to disclose the traditional process and indicate typical characteristics of Kapi-pla for preparing standard regulation and supporting next approval projects like southern gastro-democracy shortly. An insight interview indicated that each producer used his or her own ancestors’ guidelines and available fish following zero waste concept. Interestingly, the process requires a specific range of fish quality, namely soft texture and swollen sign before use. Kapi-pla showed a brown-gray of thick-clump texture with bone, spine and scale of the used fish. Amino acids composition profile determined by HPLC were classified as bitter-salty-sour (umami), sulphurous, bitter-salty-sweet, sweet-bitter and sweet taste while fatty acids profile analyzed by GC were palmitic acid, stearic acid, oleic acid and palmitoleic acid which were linked to taste sensation of Kapi-pla from each area. Results indicated that Kapi-pla from brackish-marine water fish (B-MF) (Pak Phanang, Nakhon Si Thammarat) seemed to contain more sweet amino acids including glycine, lower or even the lowest undesired taste as threonine and lysine, and less allergic precursor (histidine). In addition, it contained higher desired fatty acid composition (EPA and DHA) in comparison to others. Chemical and physical parameters obtained from this experiment were the first documentation supporting and relating to public consumer tests. All scientific parameters are proceeding to use for Kapi-pla standard regulation issued by Thai FDA later. Additionally, Thai government has been selected and appointed Kapi-pla as one of southern gastro-democracy items and planned to create several de novo menus using either alone or as an ingredient in other menus for welcome visitors and exported products further.